Diversity Temporal–Spatial Dynamics of Potato Rhizosphere Ciliates and Contribution to Nitrogen- and Carbon-Derived Nutrition in North-East China - Weibin Zheng; Xiaodan Zheng; Yuqing Wu; Shaoyang Lv; Chang Ge; Xiang Wang; Qiuhong Wang; Jingjing Cui; Nanqi Ren; Ying Chen (Plants, 2023)
Ciliates are an important component of the rhizosphere microorganism community, but their nutritional contribution to plants has not been fully revealed. In this paper, we investigated the rhizosphere ciliate community of potatoes during six growth stages, illustrated the spatial–temporal dynamics of composition and diversity, and analyzed the correlation between soil physicochemical properties. The contributions of ciliates to the carbon- and nitrogen-derived nutrition of potatoes were calculated. Fifteen species of ciliates were identified, with higher diversity in the top soil, which increased as the potatoes grew, while they were more abundant in the deep soil, and the number decreased as the potatoes grew. The highest number of species of ciliates appeared in July (seedling stage). Among the five core species of ciliates, Colpoda sp. was the dominant species in all six growth stages. Multiple physicochemical properties affected the rhizosphere ciliate community, with ammonium nitrogen (NH4+-N) and the soil water content (SWC) greatly influencing ciliate abundance. The key correlation factors of ciliates diversity were NH4+-N, available phosphorus (AP), and soil organic matter (SOM). The annual average contribution rates of carbon and nitrogen by rhizosphere ciliates to potatoes were 30.57% and 23.31%, respectively, with the highest C/N contribution rates reaching 94.36% and 72.29% in the seedling stage. This study established a method for estimating the contributions of carbon and nitrogen by ciliates to crops and found that ciliates could be potential organic fertilizer organisms. These results might be used to improve water and nitrogen management in potato cultivation and promote ecological agriculture.